A study on the key factors of csr indicators for tenderers in procurement screening using the Delphi method and DEMATEL-based analytic network process - Kuo-Yu Peng; Hsiu Li Liao (Administrative Sciences, 2022)
European Union public procurement law increasingly allows countries' authorities to take corporate social responsibility (CSR) into account in public procurement decisions. Up to 2022, few public procurements were determined by these key factors of CSR scoring items. It is worthy to study whether there is consistency in tenderers' views on CSR indicators and factors. In this study, 10 experts working in companies from different government entities were invited to participate in a questionnaire survey. In this study, a DEMATEL-based analytic network process (DANP) was applied to find out the weights of each indicator. Our finding shows the important criteria selected for tenderers were measures to support "work-life balance" for employees and "salary increase for employees". These are important responses to the problems encountered by companies in CSR practices and can be used as a reference to enhance corporations' CSR goals or pursue future sustainable business excellence.
Keywords: 350; corporate social responsibility (CSR); decision-making trial and evaluation laboratory (DEMATEL); DEMATEL-based analytic network process (DANP); employees' compensation; green procurement; public procurement